2017
DOI: 10.21668/health.risk/2017.3.03.eng
|View full text |Cite
|
Sign up to set email alerts
|

On assessing electromagnetic field (300 kmhz – 300mhz) in a large industrial city on the basis of 3d modeling and instrumental measuring

Abstract: The article dwells on issues of modeling electromagnetic fields levels (EMF with frequency equal to 300

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On several occasions [5] areas with elevated risk of adverse influence on health of mobile communication users were identified, ecological situation and possible risks for public health due to environmental contamination by electromagnetic fields of mobile communication base stations were evaluated [6]. Issues of modeling electromagnetic field (EMF) levels with 300 HHz -300 MHz frequency generated by radiotransmitters, radiolocation systems and mobile communication in a large regional center are being studied [7], new methods of background EMR intensity evaluation are being developed [8]. Generally, all studies confirm the relevance of further research for determining influence of electromagnetic fields and radiation (EMFaR) on human organism; it is shown that hazards associated with this factor are underestimated, and that there is no systemic approach to EMFaR evaluation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On several occasions [5] areas with elevated risk of adverse influence on health of mobile communication users were identified, ecological situation and possible risks for public health due to environmental contamination by electromagnetic fields of mobile communication base stations were evaluated [6]. Issues of modeling electromagnetic field (EMF) levels with 300 HHz -300 MHz frequency generated by radiotransmitters, radiolocation systems and mobile communication in a large regional center are being studied [7], new methods of background EMR intensity evaluation are being developed [8]. Generally, all studies confirm the relevance of further research for determining influence of electromagnetic fields and radiation (EMFaR) on human organism; it is shown that hazards associated with this factor are underestimated, and that there is no systemic approach to EMFaR evaluation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Issues of modeling electromagnetic field (EMF) levels with 300 HHz -300 MHz frequency generated by radiotransmitters, radiolocation systems and mobile communication in a large regional center are being studied [7], new methods of background EMR intensity evaluation are being developed [8]. Generally, all studies confirm the relevance of further research for determining influence of electromagnetic fields and radiation (EMFaR) on human organism; it is shown that hazards associated with this factor are underestimated, and that there is no systemic approach to EMFaR evaluation [7]. Impact of RF EMR on cardiovascular system (CVS) becomes a specific subject of research: moderate bradycardia was registered in adult volunteers in response to 0.9 HHz frequency EMR exposure [9], shifts in regulation of human circulatory system were found [10].…”
Section: Introductionmentioning
confidence: 99%